Blood stream infection and outcomes in recipients of a left ventricular assist device. (8th June 2020) - Angleitner, Philipp; Matic, Aleksa; Kaider, Alexandra; Dimitrov, Kamen; Sandner, Sigrid; Wiedemann, Dominik; Riebandt, Julia; Schlöglhofer, Thomas; Laufer, Günther; Zimpfer, Daniel
Abstract: OBJECTIVES: Our aim was to investigate associations between blood stream infection [≥1 positive blood culture (BC)] and outcomes in recipients of a left ventricular assist device (LVAD). METHODS: We retrospectively analysed all adult recipients of a continuous-flow LVAD between 2006 and 2016 at the Division of Cardiac Surgery, Medical University of Vienna ( n  = 257; devices: Medtronic HeartWare ® HVAD ®, Abbott HeartMate II ®, Abbott HeartMate 3™). The primary outcome was all-cause mortality during follow-up. Secondary outcomes included the risk of stroke and pump thrombus during follow-up as well as the probability of heart transplantation (HTx). Risk factors for the development of ≥1 positive BC were evaluated additionally. RESULTS: The incidence of ≥1 positive BC during the first year of LVAD support was 32.1% [95% confidence interval (CI) 26.4–37.9]. Multivariable Cox proportional cause-specific hazards regression analysis showed that a positive BC was associated with significantly increased all-cause mortality [hazard ratio (HR) 5.51, 95% CI 3.57–8.51; P  < 0.001]. Moreover, a positive BC was associated with a significantly increased risk of stroke (HR 2.41, 95% CI 1.24–4.68; P  = 0.010). There was no association with the risk of pump thrombus or the probability of HTx. Independent risk factors for a positive BC included preoperative albumin and extracorporeal membrane oxygenation/intra-aortic balloon pump support. CONCLUSIONS: Blood stream infection is common and associated with a significantly increased risk of all-cause mortality and stroke at any given time during LVAD support. Effective strategies of prevention and treatment are necessary.